Effect of Sodium Cyanide on Behaviour and Respiratory Surveillance in Freshwater Fish, Labeo rohita (Hamilton) - H.A. Sayeswara2 and Mahesh Anand Goudar3, M.S. Prashanth1, (Recent Research in Science and Technology, 2011)
The toxicity of sodium cyanide (free cyanide) to the freshwater fish, Labeo rohita was studied using static bioassay method. The LC50 in 96 h was found to be 33 Âµg/L. Behavioural changes when exposed to lethal concentration of sodium cyanide showed increased opercular movement, increased surface behaviour, loss of equilibrium, change in body colour, increased secretion of mucus, irregular swimming activity, rapid jerk movement, partial jerk and aggressiveness. The swimming behaviour was in a cork-screw palter, rotating along horizontal axis. In sub lethal treatment, the schooling behaviour of the fish was slowly disrupted, the ventilation rate was increased. The fish at 21st days of exposure exhibited balanced swimming and active feeding and behaved in normal way. Oxygen consumption was decreased in lethal concentration (-22.64 to -70.13%), but in sub lethal concentration decreased trend was improved and reached normal level at 21st day (-25.10 to -2.19). Alterations in oxygen consumption may be due to respiratory distress as a consequence of impairment in oxidative metabolism. Fish in sub lethal concentration were found under stress, but that was not fatal.